Participation of the «New» EU Member States in the European Research Programmes — A Long Way to Go - Klaus Schuch (Foresight and STI Governance, 2014)
This paper discusses the participation of the EU13 countries in European research, mainly in the European Framework Programmes for RTD. It briefly reflects on the structural challenges of the then Central European candidate countries during the transformation period in the 1990s to recall their starting-point at the time when they first became associated to the European Framework Programme for RTD. Almost 15 years after the first full association to the European Framework Programme for RTD, the actual participation situation of the ‘new’ EU member states is analysed. Next, the European Union’s measures to enhance widening participation of organizations in the ongoing European Framework Programme for RTD with the name ‘HORIZON 2020’ are concisely described. Finally, conclusions are drawn as to why – despite several efforts – participation of the EU13 is still low.